Cytotoxic activity of Kingella kingae RtxA toxin depends on post-translational acylation of lysine residues and cholesterol binding. Issue 1 (December 2018) - Osickova, Adriana; Balashova, Nataliya; Masin, Jiri; Sulc, Miroslav; Roderova, Jana; Wald, Tomas; Brown, Angela; Koufos, Evan; Chang, En; Giannakakis, Alexander; Lally, Edward; Osicka, Radim
Abstract Kingella kingae is a member of the commensal oropharyngeal flora of young children. Improvements in detection methods have led to the recognition ofK. kingae as an emerging pathogen that frequently causes osteoarticular infections in children and a severe form of infective endocarditis in children and adults.Kingella kingae secretes a membrane-damaging RTX (Repeat in ToXin) toxin, RtxA, which is implicated in the development of clinical infections. However, the mechanism by which RtxA recognizes and kills host cells is largely unexplored. To facilitate structure-function studies of RtxA, we have developed a procedure for the overproduction and purification of milligram amounts of biologically active recombinant RtxA. Mass spectrometry analysis revealed the activation of RtxA by post-translational fatty acyl modification on the lysine residues 558 and/or 689 by the fatty-acyltransferase RtxC. Acylated RtxA was toxic to various human cells in a calcium-dependent manner and possessed pore-forming activity in planar lipid bilayers. Using various biochemical and biophysical approaches, we demonstrated that cholesterol facilitates the interaction of RtxA with artificial and cell membranes. The results of analyses using RtxA mutant variants suggested that the interaction between the toxin and cholesterol occurs via two cholesterol recognition/interaction amino acid consensus motifs located in the C-terminal portion of the pore-forming domain of the toxin. Based on our observations, we conclude that the cytotoxic activity of RtxA depends on post-translational acylation of the K558 and/or K689 residues and on the toxin binding to cholesterol in the membrane.